Parental Leave and Children's Schooling Outcomes: Quasi-Experimental Evidence from a Large Parental Leave Reform - Natalia Danzer; Victor Lavy (Institute for the Study of Labor (IZA), 2013)
This paper investigates the question whether long-term human capital outcomes are affected by the duration of maternity leave, i.e. by the time mothers spend at home with their newborn before returning to work. Employing RD and difference-in-difference approaches, this paper exploits an unanticipated reform in Austria which extended the maximum duration of paid and job protected parental leave from 12 to 24 months for children born on July 1, 1990 or later. We use test scores from the Austrian PISA test of birth cohorts 1990 and 1987 as measure of human capital. The evidence suggest no significant overall impact of the extended parental leave mandate on standardized test scores at age 15, but that the subgroup of boys of highly educated mothers have benefited from this reform while boys of low educated mothers were harmed by it.
Keywords: J13; J24; J22; 330; parental leave reform; maternal employment; human capital; child development; cognitive skills; Elternzeit; Wirkungsanalyse; Kinder; Bildungsniveau; Österreich